Influence of temperature and rainfall on the population dynamics of Glycaspis brimblecombei and Psyllaephagus bliteus in Eucalyptus camaldulensis plantations - Ferreira-Filho, Pedro Jose; Wilcken, Carlos Frederico [UNESP]; Masson, Marcus Vinicius; Tavares, Wagner De Souza; Guerreiro, Julio Cesar; Do Carmo, Janaina Braga; Prado, Evandro Pereira [UNESP]; Zanuncio, Jose Cola (Soc Colombiana Entomologia-socolen, 2017)
The work analyzes the effect of temperature and rainfall on the population dynamics of Glycaspis brimble-combei (Hemiptera: Aphalaridae) and its parasitoid Psyllaephagus bliteus (Hymenoptera: Encyrtidae) in a Eucalyptus camaldulensis (Myrtaceae) plantation in Sao Paulo State, Brazil. During the study 53 yellow sticky traps were installed and 53 branches were collected from a 19 ha plot of E. camaldulensis plantation per evaluation. A total of 42 evaluations was made from January 2006 to 2008. The number of adults of G. brimblecombei and P. bliteus caught in the yellow sticky traps as well as the immature and mummies of the parasitized psyllids on E. camaldulensis leaves varied with seasons. The population also varies according to the season, with a peak in the winter and decreases in the summer when temperature and rainfall increase. The G. brimblecombei and P. bliteus populations were inversely correlated with temperature and rainfall. These results are discussed as potential limitations to the establishment of the pest and its parasitoid.
Keywords: Biological control; Forest Pest; Monitoring; Myrtaceae